SISTEM AKUNTANSI PENERIMAAN DANA WAKAF TUNAI PADA LEMBAGA AMIL ZAKAT YATIM MANDIRI TULUNGAGUNG - Eni Widhajati; Marlena Marlena; Nurul Kamaliya (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2022)
This research is based on the observations of researchers, that the accounting system is important in reporting in order to build public trust and satisfaction with funds managed by amil zakat institutions. In addition, information from an accounting system plays an important role in the company's internal and external control. The purpose of this study was to find out how the accounting system for receiving cash waqf funds and the effectiveness of the accounting system at the Amil Zakat Yatim Mandiri Tulungagung. This study uses a qualitative research approach. What is considered as the independent variable is the acceptance accounting system, while what is considered as the dependent variable is the acceptance of waqf funds. This study uses secondary data and primary data which is processed by datancollection methods through observation, interviews, and documentation. The analysisttechnique is carried out by data reduction, data display, and conclusions or verification. The results of this study indicate that the accounting system for receiving cash waqf funds has not been effective in providing individual information to donors who have contributed to Yatim Mandiri programs, it is necessary to improve the system that can provide information to donors via sms or email. There is a double job at the reception which is still empty, so it is necessary to add employees who run the admissions system.